KINERJA PROGRAM PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN CIMALAKA KABUPATEN SUMEDANG - Rohayatin, Ai (LPPM UNSAP & FISIP UNSAP, 2025)
This research aims to determine how the performance of the Integrated Administrative Services Program (PATEN) in Cimalaka District, Sumedang Regency, is functioning. The research method used in this study is qualitative research. The technique for determining informants is purposive sampling, with informants including the Head of Public Services, Administrative Population Information System (SIAK) Operators, E-ID Operators, and Population Database Administrators (ADB). The data collection techniques used include literature study and field study, which consist of observation, interviews, documentation, and triangulation. The data validity techniques used are credibility, transferability, dependability, and confirmability tests. Meanwhile, the data analysis techniques in this study include Data Collection, Data Reduction, Data Display, and Verification. Based on the research results, it was concluded that the Performance of the Integrated Administrative Services Program at the Sub-district (PATEN) in Cimalaka District, Sumedang Regency shows quite good results, although there are several crucial aspects that require further attention. There are obstacles in the implementation of the PATEN Program, namely limitations in information technology mastery, a high workload, lack of supporting facilities, and weak inter-sectoral coordination. Efforts to address these obstacles include training, task rotation, procurement of facilities, and strengthening internal coordination